Adsorption and reaction of acetylene on clean and oxygen-precovered Pd(100) studied with high-resolution X-ray photoelectron spectroscopy - Höfert, Oliver; Lorenz, Michael Peter Andreas; Streber, Regine; Zhao, Wei; Bayer, Andreas; Steinrück, Hans-Peter; Papp, Christian (Journal of Chemical Physics, 2013)
We investigated the adsorption and thermal evolution of acetylene on clean Pd(100) and Pd(100) precovered with 0.25 ML oxygen. The measurements were performed in situ by fast XPS at the synchrotron radiation facility BESSY II. On Pd(100) acetylene molecularly adsorbs at 130 K. Upon heating transformation to a CCH species occurs around 390 K along with the formation of a completely dehydrogenated carbon species. On the oxygen-precovered surface partial CCH formation already occurs upon adsorption at 130 K, and the dehydrogenation temperature and the stability range of CCH are shifted to lower temperatures by ∼200 K. © 2013 AIP Publishing LLC.

Adsorption and reaction of SO2 on clean and oxygen precovered Pd(100) - A combined HR-XPS and DF study - Luckas, Nicola; Gotterbarm, Karin; Streber, Regine; Lorenz, Michael Peter Andreas; Höfert, Oliver; Vines, Francesc; Papp, Christian; Görling, Andreas; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2011)
We studied the adsorption and reactivity of SO on clean and oxygen precovered Pd(100) with high resolution X-ray photoelectron spectroscopy and density functional calculations. Upon adsorption at 120 K two different SO species were detected, which were identified as upright-standing and flat-lying molecules by comparing the calculated core level shifts. In agreement with the relative stabilities determined by the calculations the intensities of the photoelectron spectra indicate that the majority species are upright-standing SO . Upon heating the quantitative analysis of the data indicates desorption of SO and formation of atomic sulfur. On the oxygen precovered surface small amounts of SO are formed already upon SO adsorption at low temperatures. Upon heating stepwise oxidation of SO to SO and, eventually, to SO is found. Two different SO species were detected, which are assigned to SO bound in the proximity of or remote from oxygen adatoms, according to core level shift estimates. © 2011 the Owner Societies.

CO2 activation on single crystal based ceria and magnesia/ceria model catalysts - Lykhach, Yaroslava; Staudt, Thorsten; Streber, Regine; Lorenz, Michael Peter Andreas; Bayer, Andreas; Steinrück, Hans-Peter; Libuda, Jörg (European Physical Journal B, 2010)
Novel multifunctional ceria based materials may show an improved performance in catalytic processes involving CO activation and reforming of hydrocarbons. Towards a more detailed understanding of the underlying surface chemistry, we have investigated CO activation on single crystal based ceria and magnesia/ceria model catalysts. All model systems are prepared starting from well-ordered and fully stoichiometric CeO (111) films on a Cu(111) substrate. Samples with different structure, oxidation state and compositions are generated, including CeO /Cu(111) (reduced), MgO/CeO /Cu(111) (reduced), mixed MgO-CeO /Cu(111) (stoichiometric), and mixed MgO-CeO /Cu(111) (reduced). The morphology of the model surfaces is characterized by means of scanning tunneling microscopy (STM), whereas the electronic structure and reactivity is probed by X-ray photoelectron spectroscopy (XPS). The experimental approach allows us to compare the reactivity of samples containing different types of Ce , Ce , and Mg ions towards CO at a sample temperature of 300 K. Briefly, we detect the formation of two CO -derived species, namely carbonate (CO ) and carboxylate (CO ) groups, on the surfaces of all investigated samples after exposure to CO at 300 K. In parallel to formation of the carbonate species, slow partial reoxidation of reduced CeO /Cu(111) occurs at large doses of CO . The reoxidation of the reduced ceria is largely suppressed on MgO-containing samples. The tendency for reoxidation of Ce to Ce by CO decreases with increasing degree of intermixing between MgO and CeO . Additionally, we have studied the stability of the formed carbonate species as a function of annealing temperature. © 2010 EDP Sciences, SIF, Springer-Verlag Berlin Heidelberg.

Erratum: Interaction between silver nanowires and CO on a stepped platinum surface (Journal of Chemisty Physics (2009) 131 (064702)) - Streber, Regine; Tränkenschuh, Barbara; Schöck, Johannes; Papp, Christian; Steinrück, Hans-Peter; Mcewen, J. -S.; Gaspard, P.; Denecke, R. (Journal of Chemical Physics, 2009)

Influence of steps on the adsorption and thermal evolution of SO2 on clean and oxygen precovered Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Höfert, Oliver; Zhao, Wei; Wickert, Sandra; Darlatt, Erik; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2010)
We investigated the adsorption and reaction of SO on clean and oxygen precovered, flat, and regularly stepped Pt surfaces, Pt(111), Pt(322), and Pt(355) by in situ high resolution X-ray photoelectron spectroscopy. Induced by the steps and/or the coadsorbed oxygen, several new SO species are observed, in addition to the two known SO species on Pt(111). On all investigated surfaces, a hit and stick mechanism is found for the adsorption, and no diffusion from terrace to step sites occurs at low temperatures. For the oxygen free stepped surfaces, a higher reactivity toward SO dissociation/disproportionation is found compared to Pt(111). On all three oxygen precovered Pt surfaces some SO is already formed directly upon SO exposure at low temperatures. Heating of this mixed O/SO layers first results in oxidation of more SO to SO, and at higher temperatures in subsequent oxidation of SO to SO, which finally decomposes above 450 K. The different reactions show a significant influence of the steps. © 2010 American Chemical Societ

Influence of steps on the adsorption of methane on platinum surfaces - Papp, Christian; Tränkenschuh, Barbara; Streber, Regine; Fuhrmann, Thomas; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physical Chemistry C, 2007)
The activated adsorption of methane was investigated on two stepped Pt(355) and Pt(322) surfaces by timedependent in situ high-resolution X-ray photoelectron spectroscopy (XPS) combined with a supersonic molecular beam and was compared to corresponding results on Pt(111). Both stepped surfaces have five atom row wide (111) terraces but a different step orientation, namely, (111) and (100), respectively. Independent of the kinetic energy (0.45-0.83 eV) of impinging methane (CH or CD), methyl is formed on all surfaces upon adsorption at 120 K. For the stepped surfaces, two different methyl species are identified from the XP spectra, which are attributed to adsorption at terrace sites and at step sites. The total initial sticking coefficients (for terrace + step sites) and the total coverages are very similar for all three surfaces. At low coverages, diffusion of methyl from the terraces to the steps is significantly stronger on Pt(355) than on Pt(322), and the step saturation coverage is higher on Pt(355). The thermal evolution of methyl was also investigated by in situ temperature-programmed XPS. Overall, an enhanced reactivity toward dehydrogenation to methylidyne is found for both terrace and step sites on the stepped surfaces, with the (111) steps of Pt(355) exhibiting the highest activity. © 2007 American Chemical Society.

Integrated X-ray photoelectron spectroscopy and DFT characterization of benzene adsorption on Pt(111), Pt(355) and Pt(322) surfaces - Zhang, Renqin; Hensley, Alyssa J.; Mcewen, Jean-Sabin; Wickert, Sandra; Darlatt, Erik; Fischer, Kristina; Schöppke, Matthias; Denecke, Reinhard; Streber, Regine; Lorenz, Michael Peter Andreas; Papp, Christian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2013)
We systematically investigate the adsorption of benzene on Pt(111), Pt(355) and Pt(322) surfaces by high-resolution X-ray photoelectron spectroscopy (XPS) and first-principle calculations based on density functional theory (DFT), including van der Waals corrections. By comparing the adsorption energies at 1/9, 1/16 and 1/25 ML on Pt(111), we find significant lateral interactions exist between the benzene molecules at 1/9 ML. The adsorption behavior on Pt(355) and Pt(322) is very different. While on Pt(355) a step species is clearly identified in the C 1s spectra at low coverages followed by occupation of a terrace species at high coverages, no evidence for a step species is found on Pt(322). These different adsorption sites are confirmed by extensive DFT calculations, where the most favorable adsorption configurations on Pt(355) and Pt(322) are also found to vary: a highly distorted across the step molecule is found on Pt(355) while a less distorted configuration adjacent to the step molecule is deduced for Pt(322). The theoretically proposed C 1s core level binding energy shifts between these most favorable configurations and the terrace species are found to correlate well with experiment: for Pt(355), two adsorbate states are found, separated by ∼0.4 eV in XPS and 0.3 eV in the calculations, in contrast to only one state on Pt(322). © 2013 the Owner Societies.

Interaction between silver nanowires and CO on a stepped platinum surface - Streber, Regine; Tränkenschuh, Barbara; Schöck, Johannes; Papp, Christian; Steinrück, Hans-Peter; Mcewen, J. -S.; Gaspard, P.; Denecke, Reinhard (Journal of Chemical Physics, 2009)
We studied the interplay between Ag decoration of a stepped Pt(355) surface and CO adsorption by in situ high-resolution x-ray photoelectron spectroscopy. Varying amounts of Ag deposited at 300 K initially lead to a row-by-row growth starting from the lower Pt step edges. Such decoration of the step sites results in a change in the CO adsorption behavior. An apparent blocking of step sites for low CO coverages is attributed to a change in the electronic structure, resulting in a C 1s binding energy of CO at step sites being equal to that for CO at terrace on-top sites in the presence of Ag. Higher CO coverages induce the formation of embedded Ag clusters within the upper terraces, thus freeing up a part of the original Pt step sites for CO adsorption, as was derived by a comparison to density functional theory calculations in the corresponding surface models. © 2009 American Institute of Physics.

Kinetic passivation of steps with sulfur and CO/S site exchange processes on stepped Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2008)
We studied the influence of preadsorbed sulfur on the adsorption of CO on Pt(3 5 5) and Pt(3 2 2) by in situ X-ray photoelectron spectroscopy. At low temperatures, no adsorption of CO at steps is found, indicating a passivation by sulfur. Upon heating, population of step sites with CO occurs. This behavior is attributed to a kinetic passivation of the steps by sulfur at low temperatures, which is lifted upon heating. The characteristic transition temperatures of 185 K for Pt(3 5 5) and 240 K for Pt(3 2 2) are significantly different, due to a higher activation barrier for the CO/S site exchange process for Pt(3 2 2). © 2007 Elsevier B.V. All rights reserved.

Kinetics of the sulfur oxidation on palladium: A combined in situ x-ray photoelectron spectroscopy and density-functional study - Gotterbarm, Karin; Luckas, Nicola; Höfert, Oliver; Lorenz, Michael Peter Andreas; Streber, Regine; Papp, Christian; Vines, Francesc; Steinrück, Hans-Peter; Görling, Andreas (Journal of Chemical Physics, 2012)
We studied the reaction kinetics of sulfur oxidation on the Pd(100) surface by in situ high resolution x-ray photoelectron spectroscopy and ab initio density functional calculations. Isothermal oxidation experiments were performed between 400 and 500 K for small amounts (∼0.02 ML) of preadsorbed sulfur, with oxygen in large excess. The main stable reaction intermediate found on the surface is SO , with SO and SO being only present in minor amounts. Density-functional calculations depict a reaction energy profile, which explains the sequential formation of SO , SO , and eventually SO , also highlighting that the in-plane formation of SO from S and O adatoms is the rate limiting step. From the experiments we determined the activation energy of the rate limiting step to be 85 6 kJ mol by Arrhenius analysis, matching the calculated endothermicity of the SO formation. © 2012 American Institute of Physics.

Microscopic insights into methane activation and related processes on Pt/Ceria model catalysts - Lykhach, Yaroslava; Staudt, Thorsten; Lorenz, Michael Peter Andreas; Streber, Regine; Bayer, Andreas; Steinrück, Hans-Peter; Libuda, Jörg (ChemPhysChem, 2010)
Ceria-based supported noble-metal catalysts release oxygen, which may help to reduce the formation of carbonaceous residues, for example during hydrocarbon reforming. To gain insight into the microscopic origins of these effects, a model study is performed under ultrahigh-vacuum conditions using single-crystal-based supported model catalysts. The model systems are based on ordered CeO (111) films on Cu(111), on which Pt nanoparticles are grown by physical vapor deposition. The growth and structure of the surfaces are characterized by means of scanning tunneling microscopy, and the electronic structure and reactivity are probed by X-ray photoelectron spectroscopy. Specifically, it is shown that the fully oxidized CeO thin films undergo slight reduction upon Pt deposition (CeO ). This effect is enhanced upon annealing (CeO ), thus indicating facile oxygen release and reverse spillover. The model system is structurally stable up to temperatures exceeding 700 K. The activation of methane is investigated using high-kinetic-energy CH (0.83 eV), generated by a supersonic molecular beam. It is shown that dehydrogenation occurs under rapid formation of CH or C species without detectable amounts of CH being formed, even at low temperatures (100 K). The released hydrogen spills over to the CeO support, which leads to the formation of OH groups. At 200 K and above, the OH groups start to decompose leaving additional Ce centers behind (CeO ). At up to 700 K, carbon deposits are quantitatively removed by reaction with oxygen, which is supplied by reverse spillover from the CeO film, thus leading to substantial reduction of the support ( CeO ). © 2010 Wiley-VCH Verlag GmbH& Co. KGaA, Weinheim.
Keywords: cerium oxide; heterogeneous catalysis; methane dehydrogenation; supported catalysts; platinum

Oxidation of stepped Pt(111) studied by x-ray photoelectron spectroscopy and density functional theory - Bandlow, Jochen; Kaghazchi, Payam; Jacob, Timo; Papp, Christian; Tränkenschuh, Barbara; Streber, Regine; Lorenz, Michael Peter Andreas; Fuhrmann, Thomas; Denecke, R.; Steinrück, Hans-Peter (Physical Review B, 2011)
In this comparative density functional theory and x-ray photoelectron spectroscopy study on the interaction of oxygen with stepped Pt(111) surfaces, we show that both the initial adsorption and oxidation occur at the steps rather than terraces. An equivalent behavior was observed for the oxide formation at higher chemical potentials, where, after the formation of a one-dimensional PtO-type oxide at the steps, similar oxide chains form on the (111) terraces, indicating the initial stages of bulk oxide formation. © 2011 American Physical Society.

Site blocking and CO/sulfur site exchange processes on stepped Pt surfaces - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Wickert, Sandra; Schöppke, Matthias; Denecke, Reinhard; Steinrück, Hans-Peter (Journal of Physics: Condensed Matter, 2009)
The influence of preadsorbed sulfur on the adsorption of CO on Pt(355) and Pt(322) is investigated systematically for sulfur precoverages between 0.02 and 0.30ML by insitu x-ray photoelectron spectroscopy of the C 1s and S 2p core levels. The two surfaces have the same nominal terrace width of 5 atomic rows, but different step orientation. For both, at low temperatures (130 and 150K), S preferentially adsorbs at the steps and passivates them for COadsorption. The required S precoverage is significantly smaller for Pt(322), because of the lower number of steps as a result of the S-induced double-step formation. Upon heating, population of step sites with CO occurs due to irreversible CO/S site exchange. At low S precoverages, the characteristic transition temperatures of 165K for Pt(355) and 245K for Pt(322) are significantly different, indicating a higher activation barrier for the CO/S site exchange process for Pt(322). For medium to high S precoverages the transition temperature stays unchanged for Pt(322) but increases for Pt(355). The observed behavior is attributed to a kinetic passivation of the steps by sulfur at low temperatures, which is lifted upon heating. © 2009 IOP Publishing Lt

SO2 adsorption and thermal evolution on clean and oxygen precovered Pt(111) - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Höfert, Oliver; Darlatt, Erik; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2010)
We studied the adsorption and reaction of sulfur dioxide on clean and oxygen precovered platinum surfaces by in situ high resolution X-ray photoelectron spectroscopy and discuss earlier, contradicting results. On the clean surface we find flat lying and upright standing SO, adsorbing in similar amounts at low temperature. Upon heating, the ratio changes strongly favoring the standing SO; subsequently almost all SO desorbs. On the oxygen precovered surface the standing SO is preferably populated and even at low temperatures a direct reaction of SO to SO occurs. Upon heating, SO oxidation to SO and subsequently to SO is found. © 2010 Elsevier B.V. All rights reserve

Sulfur oxidation on Pt(355): It is the steps! - Streber, Regine; Papp, Christian; Lorenz, Michael Peter Andreas; Bayer, Andreas; Denecke, Reinhard; Steinrück, Hans-Peter (Angewandte Chemie International Edition, 2009)
Steps in the right direction: The role of steps in the removal of sulfur from a Pt model catalyst via metastable SO and SO species, was demonstrated by in situ high-resolution X-ray photoelectron spectroscopy. From isothermal experiments the activation energy of the rate-determining step was deduced to be 34 kJmol. © 2009 Wiley-VCH Verlag GmbH &. Co. KGaA.